NETRALITAS BIROKRASI DALAM PEMILIHAN KEPALADAERAH - Alizar Isna (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2010)
Abstract: This study aimed to describe the bureaucratic neutrality in the election in Indonesia, and effortsto improve the neutrality of these. Literature study was conducted by doing a search of documentsand review of related research results bureaucratic neutrality in the election in Indonesia as well asaspects ofthe employment ofcivil servants, especially thejob competency and competency standards.Weaknesses in aspects of personnel administration that allows the regents through personalitynya, andsupported by vested interests, political speculation, and power is expected by the civil servants whoprovide political support to the contestants election, has led to the bureaucracy involved in the election.There shoutd be clear guidelines for career development and performance appraisal ofcivil servants toprovide opportunities for the emergence of objektiovitas regent / mayor in the recruitment of officerswithin the district / city.